KONSEP TIJAROH SEBAGAI SOLUSI FENOMENA PERDAGANGAN DENGAN SISTEM TEBAS TERHADAP KOMODITAS PADI DAN MANGGA DI KABUPATEN NGAWI - Hanafi, Yusron (LPPM STAI Muhammadiyah Probolinggo, 2024)
The total area of Ngawi Regency is 1,298.58 km2, of which 506.6 km2 or about 40% is made up of rice fields. According to the data, farmers employ the bulk of Ngawi people. Mango fruit is the second most abundant good after rice, as most Ngawi people grow mango trees in front or behind their homes. When harvest season rolls around, farmers have trouble finding buyers who will purchase their crops in an honest and profitable manner. This is because buyers, also known as penebas, use the Tebas system to complete the purchase process for these two commodities, which means that the system cannot fulfill the wishes of both parties involved in the transaction if It also goes by the name